Cumulative Risks of Excipients in Pediatric Phytomucolytic Syrups: The Implications for Pharmacy Practice - Kateryna O. Zupanets; Sergii K. Shebeko; Kseniia L. Ratushna; Oleksandr V. Katilov (MDPI AG, 2021)
Expectorant phytomucolytic syrups are widely used pediatric OTC-medicines. Physicians, pediatricians, and pharmacists are traditionally concerned with the efficacy of the active ingredients in cough syrups, and rarely consider the safety aspects of excipients that however are not absolutely "inactive" and are proved to initiate some negative reactions and interactions with other drugs. This paper presents a review, categorization, and comparative analysis of the safety profile of excipients contained in the 22 best-selling OTC pediatric phytomucolytic syrups available in pharmaceutical markets in Ukraine and Germany and proposes an approach to the consideration of the excipients' safety risks for a pharmacist in the process of pharmaceutical care. The study has revealed that only one of the twenty-two analyzed syrups does not contain any potentially harmful excipients. The results of this analysis were used for developing a specific decision tool for pharmacists that can be used for minimizing excipient-initiated reactions when delivering OTC phytomucolytic syrups for children.